2010
DOI: 10.1074/jbc.m110.128926
|View full text |Cite
|
Sign up to set email alerts
|

Fetuin-A (α2HS-Glycoprotein) Is a Major Serum Adhesive Protein That Mediates Growth Signaling in Breast Tumor Cells

Abstract: The identity of the cell adhesive factors in fetal bovine serum, commonly used to supplement growth media, remains a mystery due to the plethora of serum proteins. In the present analyses, we showed that fetuin-A, whose function in cellular attachment in tissue culture has been debated for many years, is indeed a major serum cell attachment factor particularly for tumor cells. We are able to report this because of a new purification strategy that has for the first time given us a homogeneous protein band in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 44 publications
9
82
0
Order By: Relevance
“…Expression of Annexin A6 at the cell surface has been reported in numerous studies; as a receptor for chondroitin sulfate chains (Takagi et al, 2001), in association with S100A8/A9 in the cytoplasm (Bode et al, 2008) and the serum adhesive protein, fetuin-A (Sakwe et al, 2010). This is in agreement with the both immunofluorescence and immunohistochemistry results obtained in this study, showing strong 9E1 reactivity to the cell membrane.…”
Section: Annexin A6supporting
confidence: 82%
“…Expression of Annexin A6 at the cell surface has been reported in numerous studies; as a receptor for chondroitin sulfate chains (Takagi et al, 2001), in association with S100A8/A9 in the cytoplasm (Bode et al, 2008) and the serum adhesive protein, fetuin-A (Sakwe et al, 2010). This is in agreement with the both immunofluorescence and immunohistochemistry results obtained in this study, showing strong 9E1 reactivity to the cell membrane.…”
Section: Annexin A6supporting
confidence: 82%
“…Other studies indicated that AnxA6 acted as an adhesion receptor to fetuin-A (α2 HS-glycoprotein), a major serum adhesive protein on the surface of BC cells, by mediating growth signaling (43,44). AnxA6 has been observed to promote the invasiveness of BT-549 BC cells, which express higher levels of AnxA6 than MCF-10A cells, since the depletion of AnxA6 in BT-549 cells reduced their motility and abolished invasiveness (34,35).…”
Section: Multiple Functions Of Anxa6 In Breast Cancermentioning
confidence: 99%
“…This mechanism was supported by data showing that dynosore, an inhibitor of the small GTPase dynamin, did not affect fetuin-A uptake, whereas uptake of a clathrin-dependent protein, transferrin, was inhibited by 50% (Online Figure IB) and no colocalization of internalized fetuin-A with clathrin was observed (Online Figure IC). Additionally, small interfering RNA knockdown of the putative fetuin-A endocytic receptors, annexin A2 and annexin A6, 18 had no effect on fetuin-A delivery to the early endosomes (Online Figure IIA-IIC).…”
Section: Fetuin-a Is Recycled By Vsmcs Via Late Endosomal/mvb Compartmentioning
confidence: 99%